2021
DOI: 10.1080/10826084.2021.1901932
|View full text |Cite
|
Sign up to set email alerts
|

High School Intramural Participation and Substance Use: A Longitudinal Analysis of COMPASS Data

Abstract: Background: There is an association between sports participation and substance use. However, there is some evidence that intramural sports in high school may not have the same effect. Therefore, the objective of this research was to examine the longitudinal associations between intramural participation in high school and substance use. Methods: This study used a three-year linked sample (2016-2018) of grade 9 and 10 (ages 13-17) Canadian high school students in the COMPASS (Cannabis use, Obesity, Mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…When assessing cannabis use in high-school aged boys, 3 studies reported no difference in cannabis use between athletes and nonathletes, 2,15,19 while 2 other studies found less cannabis use among male athletes. 79,80 In female high-school athletes, the data are similarly contradictory. Four studies reported sports participation was associated with decreased use, 2,15,19,79 1 study found no difference in use related to sports participation, 80 and 1 study reported marijuana use was more likely in female athletes compared with their nonathlete peers.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…When assessing cannabis use in high-school aged boys, 3 studies reported no difference in cannabis use between athletes and nonathletes, 2,15,19 while 2 other studies found less cannabis use among male athletes. 79,80 In female high-school athletes, the data are similarly contradictory. Four studies reported sports participation was associated with decreased use, 2,15,19,79 1 study found no difference in use related to sports participation, 80 and 1 study reported marijuana use was more likely in female athletes compared with their nonathlete peers.…”
Section: Epidemiologymentioning
confidence: 99%
“…79,80 In female high-school athletes, the data are similarly contradictory. Four studies reported sports participation was associated with decreased use, 2,15,19,79 1 study found no difference in use related to sports participation, 80 and 1 study reported marijuana use was more likely in female athletes compared with their nonathlete peers. 39 In addition, 1 study noted that race may influence cannabis use among athletes, reporting that White female athletes were significantly more likely to use cannabis than White female nonathletes, and they also used more cannabis than non-White athletes.…”
Section: Epidemiologymentioning
confidence: 99%
“…The differences in results for sport participation may be due to the different types of sport (individual vs. team) and levels (e.g., non-competitive school vs. competitive; school vs. community-based) that could be played, and the psychosocial mechanisms may be different depending on these variations in sport types ( 21 , 23 ). Finally, much like the physical activity literature, prospective studies have provided evidence for the preceding nature of sport participation and its association with substance use ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%